The Influence of understanding basic training participants of teacher civil servants about ASN function to teacher performance in learning services - Budi Sukmajadi (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2020)
The purpose of this study was to determine the effect of Latsar CPNS participants' understanding of the function of ASN (Variable X) on the performance in learning services (Variable Y). Gibson and Spencer stated that performance is influenced by variables of employee knowledge and understanding. The research hypothesis is suspected that there is an influence of variable X on Y. The research was conducted using quantitative methods. The population was 1851 people. Samples based on the Slovin formula were taken as many as 329. The instrument tested with SPSS 18 which is declared valid and reliable. Data normality test, with the Kolmogorov-Smirnov test with a value of 0.2 for Variable X and 0.1 for Variable Y less than p 0.05, so the data for the two variables were normally distributed. Simple Linear Regression Test obtained a significance value (Sig.) of 0.012, smaller than the probability of 0.05, which means that there is a significant effect of variable X on variable Y. Furthermore, the Hypothesis Test is continued with the t test, and the t value is 2.524 greater than t table 1.6499 with R Square 0.019. The contribution of variable X to variable Y is only 1.9%. The contribution of other variables that affect the performance of CPNS teachers by 98.1% still needs further research. This study concludes that there is a positive influence on the understanding of Latsar CPNS teachers about the function of ASN on teacher performance in learning services.